Waves - Webb, Rebecca Norris 1956- (Radius Books, 2022)
Inspired by Virginia Woolf's novel The Waves, this collaborative project brings together the work of creative partners Alex Webb and Rebecca Norris Webb. This intimate collection serves as a pandemic logbook in words and images, created while the couple was largely sequestered on Cape Cod from March 2020 through May 2021. Rebecca provides original, hand-written poetry that punctuates her lyrical photographs and Alex?s panoramic seascapes. Their images serve as poignant meditations on what it means to be both deeply connected to the world around us and profoundly isolated from much that we hold dear